Osteochondroma of the distal humerus: A rare location (Indian Journal of Case Reports, 2024)
Osteochondroma of the medial condyle of the humerus is rare; hence, diagnosis can be challenging as it may be confused with other causes of swelling around the elbow joint. This can lead to compression of neurovascular structure. We present a case of left medial condyle humerus osteochondroma with ulnar nerve involvement and conduct a literature review of this rare condition. A 25-year-old male patient presented with swelling around the left elbow joint for 1 year and tingling and numbness along ulnar nerve distribution for the last 3 months. He underwent an X-ray, magnetic resonance imaging, electromyography, and nerve conduction velocity that confirmed the diagnosis of an osteochondroma with ulnar nerve involvement. An excisional biopsy was subsequently done. In conclusion, the case is an atypical location of osteochondroma. The history, clinical presentation, diagnostic imaging, and management outlined may help in the early identification and management of this rare but complicated condition.